Pengabdian dan Pengembangan Inovasi Pelaku Usaha Mikro Kecil dan Menengah di Daerah Kecamatan Jetis Pingit Kota Yogyakarta - Korain, Loisa; As’ari, Hasim (Sahabat Publikasi, 2024)
This treatment was carried out in the Jetis Pingit sub-district, Yogyakarta City. Micro, small and medium enterprises (MSMEs) are a reliable part of the economy and their existence is highly regarded. MSMEs make a sufficient contribution to the Indonesian economy, especially in Jetis Pingit District, Yogyakarta City, which can absorb labor and reduce labor in the Pingit area. The existence of MSMEs can play an important role in the Indonesian economy, because they make a significant contribution, especially in the formation of gross domestic product and employment energy absorption. There are many problems faced by MSMEs in the continuity of their business, especially from understanding MSME development strategies. This service aims to identify MSME players in creating their own business development strategies and further develop their businesses more advanced. In this strategy, can MSME players carry out this strategy better in developing MSMEs? The method used in this service is the question and answer method or direct interview. The results of this implementation can be expected for MSME actors to be able to carry out good strategies in developing MSEs. In developing products for MSMEs in Jetis Kampung Pingit that are advanced and beneficial for all, the activities carried out in Kampung Pingit are held smoothly and very well. In product development for MSMEs in Jetis Kampung Pingit.